Understanding the Influences of the Mathematics Direct Curriculum and Teaching Strategies on Students’ Attainment among Cycle Three Public School in Ras Al Khaimah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Education can become an effortless process when it is done willingly.A popular Arab expression states: "Brains that think brightly have bright futures!" students today are significantly better than they were in the past; they are more advanced in their instruction and more capable of absorbing the learning methods that are employed with them. Learning is the the underpining of life, teaching supports learning, and a curriculum provides the essence of teaching. What’s a curriculum, you may ask? A curriculum is defined as the plan that is used in education direct teachers. The tool that is used to help teachers pace their lessons is named “curriculum guide”. The first step in the curriculum is “the model”. The model determines the types of curricula used in educational philosophical approaches to teaching and methodology. Curriculum models can break down into the product model and the process model. The product model focuses on the finished product more than what happens during the learning process, while the process model focuses on how things happen in the learning process. Reform in the curriculum is key to the success of the UAE’s search for excellence in education. This study seeks to illuminate the success of this initiative in Ras Al Khaimah’s mathematics curriculum and student activities. The study will first explore the curriculum and supporting textbooks. The key players in the reform will be interviewed. This case study has implications for the study of the curriculum in a highly prescriptive centralized governed educational system that has specifically stated a plan to enhance achievement in Mathematics.The researcher adopted a sequential, mixed-method, explanatory design with two periods of data collection. First, randomly sampled Mathematics teachers from public schools in Ras Al-Khaimah and Dubai were sent internet questionnaires. The data was then analyzed using the (SPSS) software package for both descriptive and inferential statistics. Subsequently, semi-structured interviews were conducted with a subset of the sample population which was determined based on the interpretation of the quantitative data. This data was then subjected to numerous levels of coding for content analysis to provide better context and explanation for the quantitative findings.All that to find a way to refill the gap between the curriculum, teaching strategies and the students attainment. This study focused on the influence of curriculum and instructional practices on student achievement in public schools in Ras Al-Khaimah, United Arab Emirates.